2018
DOI: 10.1080/09593330.2018.1459874
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment for nutrient removal with Ecuadorian native microalgae

Abstract: The aim of this project was to study the feasibility of utilizing native microalgae for the removal of nitrogen and phosphorus, as a potential secondary wastewater treatment process in Ecuador. Agitation and aeration batch experiments were conducted using synthetic secondary wastewater effluent, to determine nitrogen and phosphorus removal efficiencies by a native Ecuadorian microalgal strain. Experimental results indicated that microalgal cultures could successfully remove nitrogen and phosphorus. [Formula: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The analysis of physico-chemical parameters was conducted, as described in Benitez et al [ 23 ] and Grube et al [ 37 ], according to the standardized protocols for analysis of water and wastewater [ 33 ]. The values of each parameter were obtained by triplicate measurements of each analyzed river sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of physico-chemical parameters was conducted, as described in Benitez et al [ 23 ] and Grube et al [ 37 ], according to the standardized protocols for analysis of water and wastewater [ 33 ]. The values of each parameter were obtained by triplicate measurements of each analyzed river sample.…”
Section: Methodsmentioning
confidence: 99%
“…This study also revealed an increase in pollutant concentrations in the surroundings of Quito [ 21 ]. Most water quality studies utilize biological indicators such as Escherichia coli and total coliform counts [ 23 , 24 ]. However, other potentially pathogenic microorganisms can be identified in the recollected samples and used as biological indicators, such as Salmonella , Pseudomonas , Shigella , and Legionella spp., as well as parasites, Giardia and Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Effective remediation processes are required to reduce the concentration of nutrients, such as nitrogen and phosphorus, and organic matter in municipal and industrial wastewaters, hence the use of microalgae has emerged as a promising strategy capable of eliminating pollutants [116]. The removal of nitrogen and phosphorous is very important to prevent eutrophication in receiving water bodies, reduce ammonia toxicity to fish, and prevent interference with free chlorine that is essential for drinking water treatment [117]. The use of microalgae for the removal of nutrients and organic matter from wastewater effluents was recently reviewed [118,119].…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…As a result of these sedimentation rate limitations, wastewater-based cultivation methods have also been investigated in an attempt to reduce the production costs associated with cultivation (Cheng et al, 2019). Wastewater contains inorganic materials required for microalgal growth such as nitrogen and phosphorous (Benítez et al, 2019). To purify wastewater, nitrogen, and phosphorous must be removed; thus, the cultivation of microalgae using wastewater can be used to simultaneously purify wastewater and produce biomass at a low cost (Benítez et al, 2019;Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater contains inorganic materials required for microalgal growth such as nitrogen and phosphorous (Benítez et al, 2019). To purify wastewater, nitrogen, and phosphorous must be removed; thus, the cultivation of microalgae using wastewater can be used to simultaneously purify wastewater and produce biomass at a low cost (Benítez et al, 2019;Cheng et al, 2019). Furthermore, bacteria can be cultured together with microalgae during cultivation with wastewater (Kwon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%